CHANGES OF THE MARKETING ENVIRONMENT IN ENTERPRISES FUNCTIONALITY ON THE B2B MARKET - BOYCHUK, Inna (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The purpose of the article is to study the changes in the conditions of the marketing environment of the enterprises functioning in the B2B market in order to determine new directions for managing their activities, which is especially relevant during the war, when domestic business suffered from many difficulties.The article states that due to the full-scale aggression of Russia, many enterprises were destroyed, there are significant restrictions on production, some companies found themselves in temporarily occupied territories without access to them, which forced them to look for new channels of promotion in the markets. It is indicated that, under such conditions, it is imperative to find such a format for the functioning of enterprises, which can ensure the maximum conservation of capacities and resources, and will allow to determine new directions of work. Entrepreneurial attitudes and the main parameters of the marketing environment of the business entities functioning were analyzed on the basis of official analytical studies. The specifics of state support for business, which were implemented through the tools of tax and monetary policy, and shown their effectiveness only partially during the martial law, are indicated. Domestic entrepreneurs had to adapt quickly to new business realities, under such conditions. The regional disproportions of the influence of active hostilities on the change of the marketing environment on the B2B market are emphasized, which negatively affected horizontal and vertical connections between enterprises, the reconfiguration of which requires a long time and significant resources. The most important problems, which are typical for domestic enterprises during the war, are identified, and recommendations are given to facilitate the functioning of B2B business in the conditions of the current marketing environment. The expediency of business adaptation due to the skillful use of Internet marketing, which allows attracting more users to the goods and services offered by enterprises, is noted. It is also suggested constant maintenance of communication with your teams to save the staff and labor. Conclusions made about the need in changing the marketing strategies and methods of business promotion on the B2B market, in determining the priority areas of enterprise functioning with their corresponding adjustment to the wartime conditions, were made.
Keywords: marketing environment; enterprises; B2B market; business; marketing activity; internet marketing; teamwork; communication support